Product Characteristics of 100% Recycled Polypropylene Plastic - Karnova Yanel (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
Plastics can be grouped into two groups, thermoplast plastics and thermoset plastics. Thermoplast plastic is a plastic that can be molded over and over again in the presence of heat. Thermoplast plastics include PE (Polyethylene), PP (Polypropylene), PS (Polystyrene), ABS (Abutile Butadine Styrene), Nylon, PET (Polyethylene Terephthalete), POM (Polyacetal), PC (Polycarbonate), etc. At process of making vases that presented in this work, the plastic material used is PP. To investigate the characteristics of the resulting product, the mechanical characteristics of the print are tested by tensile testing. By using 100% recycled PP waste raw materials using hand molding, it turned out to be successful and became a new product (flower vase) that can be utilized. But, there are decrease in the quality of virgin plastic about 31.7% of modulus of elasticity value, 94.81% of stress value and 91% of strain value. From the tensile test results, it can be concluded that the recommended printing temperature is 220 oC.